2007
DOI: 10.1080/01496390701446449
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Hydrocarbons from Crude Oil Tank Bottom Sludges using Supercritical Ethane

Abstract: A custom-built, solvent recirculating, supercritical fluid extraction (SFE) apparatus was used to study the extraction of hydrocarbons from a crude oil tank bottom sludge (COTBS) with supercritical ethane. The SFE experiments were carried out varying the pressure (10 MPa and 17.20 MPa) and temperature (358C and 658C). The yield of the extracted hydrocarbon fraction increased with increase in extraction pressure at constant temperature, and decreased with increase in extraction temperature at constant pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Also, cyclohexane had high ORR values at 2:1 C/OS ratio with Triton X-114 (63% ± 3) and rhamnolipid (63% ± 2). These values are higher compared to other studies (Biceroglu 1994;Avila-Chavez et al 2007;Zubaidy and Abouelnasr 2010;Hu et al 2015;Hu et al 2017;Nezhdbahadori et al 2018). These authors reported ORR values lower than 60%.…”
Section: Resultscontrasting
confidence: 65%
“…Also, cyclohexane had high ORR values at 2:1 C/OS ratio with Triton X-114 (63% ± 3) and rhamnolipid (63% ± 2). These values are higher compared to other studies (Biceroglu 1994;Avila-Chavez et al 2007;Zubaidy and Abouelnasr 2010;Hu et al 2015;Hu et al 2017;Nezhdbahadori et al 2018). These authors reported ORR values lower than 60%.…”
Section: Resultscontrasting
confidence: 65%
“…Many of these volatile compounds are known of suspected carcinogens and mutagens and their release into the air poses a significant threat to the ecosystem and human population. Moreover, If COTBS is disposed of inappropriately, the oily sludge will splash into the soil where hundreds of individual compounds will contaminate the soil [11,13,14]. As many of COTBS hydrocarbon components are considered as toxic, mutagenic or carcinogenic [15], in 1992 the United States Environmental Protection Agency (US EPA) announced a final rule (57 FR 37194,37252) stating treatment regulations and standards under the land disposal restrictions program for several hazardous wastes including hydrocarbon materials (COTBS) [16].…”
Section: Journal Of Advanced Chemical Engineeringmentioning
confidence: 99%
“…Perhaps the most effective approach is to utilize the sludge intact, for example in building or embedding materials, as this can completely avoid the technical problems otherwise experienced during hydrocarbon extraction processes, such as demulsication, desorption and separation. 5,6 Hassan et al 7,8 investigated the potential uses of petroleum-contaminated soil (PCS) in highway construction.…”
Section: Introductionmentioning
confidence: 99%